Analysis and survey of the application of solar dryers in eastern Nigeria - Okala, Nwoke O.; Chigasa, Uzoma C.; Cynthia, Ibeto; Chidimma, Okpara; Chibueze, Nnaji; Onuoragbunam, Obi I.; Ogbonna, Oparaku U. (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: A survey on the use of solar dryers for drying purposes was carried out in some communities in eastern Nigeria. ?The objective of the study was to ascertain the extent uses of solar dryers by local farmers and the rural populace. ?The survey method included oral interview and questionnaire administration. ?The results of the study revealed that the practical use of solar dryers is absent domestically and industrially. ?However, great enthusiasm was shown by the farmers in the use of solar crop dryers if their performance is satisfactory with respect to quality and quantity of products dried at a given time interval. ?Most farmers rejected the idea of establishing communally maintained and operated systems but preferred commercialized systems where payments are made per unit quantity of products dried. ?The study therefore recommends the development of affordable solar crop dryers with auxiliary heat sources to mitigate the effects of daily and seasonal fluctuation in solar radiation in order to cope with the demands of a profit oriented commercial drying system. ?Such a system holds a lot of promises for entrepreneurs. Keywords: crop drying, solar crop dryers, auxiliary heat sources, entrepreneurs, Nigeria DOI: 10.3965/j.issn.1934-6344.2011.03.079-082 ? Citation: Nwoke O Okala, Uzoma C Chigasa, Ibeto Cynthia, Okpara Chidimma, Nnaji Chibueze, Obi I Onuoragbunam, Oparaku U Ogbonna. ?Analysis and survey of the application of solar dryers in eastern Nigeria. ?Int J Agric & Biol Eng, 2011; 4(3): 79